2017
DOI: 10.20453/rnp.v79i4.2974
|View full text |Cite
|
Sign up to set email alerts
|

Trastornos mentales en estudiantes de medicina humana en tres universidades de Lambayeque, Perú.

Abstract: Los trastornos de salud mental son un problema muy frecuente en la población actual, sobre todo en alumnos de educación superior que, de acuerdo a algunos estudios, pueden mostrar mayor predisposición a problemas emocionales y psicosociales. Objetivos: Describir los   trastornos mentales más frecuentes en estudiantes de medicina de tres universidades de Lambayeque, durante el año 2012. Material y métodos: Estudio descriptivo transversal. La población fue de 998 alumnos distribuidos según año de estudio académi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…Previous studies corroborate this result [24][25][26]. This is consistent with the results of Sanchez-Marín et al ( 2016), who found that 17.3% of students presented some depressive episode [27]. In Peru, 13.5% were found to have some degree of depression [28].…”
Section: Prevalence Of Mental Health Disorderssupporting
confidence: 89%
“…Previous studies corroborate this result [24][25][26]. This is consistent with the results of Sanchez-Marín et al ( 2016), who found that 17.3% of students presented some depressive episode [27]. In Peru, 13.5% were found to have some degree of depression [28].…”
Section: Prevalence Of Mental Health Disorderssupporting
confidence: 89%
“…Consistently with other studies, females had a higher level of anxiety with regard to males. 1,2,10,[31][32][33] This asymmetry may be due to cultural, neurophysiological and evolutionary factors that make women more susceptible to anxiety. 34 A novel finding is that anxiety in males did not differ between semesters, while females in advanced semesters were more anxious.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found a higher prevalence of suicide risk than the reported in previous national studies . This shows a worrying trend and might be related to the increase in the number of medical students and medical schools in our country .…”
Section: Discussionmentioning
confidence: 99%